Electricity Supply Dynamics and Economic Growth in Nigeria: Evidence from an Error Correction Model (1980-2021). (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This research study investigates the impact of electricity supply dynamics and economic growth in Nigeria: evidence from an Error Correction Model (1980 – 2021). The study examined the effects of electricity demand-supply gaps, electricity pricing per capita, lending interest rates, and disposable income on GDP. Result of ADF unit root test confirm that all variables were integrated of order one (I(1)); and this necessitated the test for long-run relationship. Thus, the cointegration result shows that there is one cointegrating equation ie trace statistics (83.73255) is greater than their respective critical value (69.81889) at 5% level of significance, hence there is a long-run equilibrium relationship among the variables. The ECM results reveal that power outages significantly reduce economic growth as a million MWh of deficit in electricity demand reduces GDP by 7600.8billion Naira, while disposable income positively and significantly drives growth. Interestingly, lending interest rates show a positive relationship with GDP, contrary to conventional expectations, possibly reflecting credit expansion during periods of economic optimism. Electricity pricing exhibited a negative but statistically insignificant effect. The findings highlight the importance of reliable power infrastructure, income-enhancing fiscal policies, and balanced energy pricing strategies for fostering inclusive economic growth in Nigeria. Therefore, the study recommends for governments’ increasing investments in Energy/Electricity infrastructure in order to enhance energy supply and hence reduce power outages, benefiting all sectors of the economy. Also, there is need to advocate for full privatization of the Nigeria’s energy sectors including electricity generation and the downstream.